Redução da incrustação em fornos industriais através da produção de briquetes com resíduos de biomassa de macrófitas aéreas associadas a resíduo de gesso - Silva, Devanchirles Maria da (2017)
The calorific value of the direct combustion of briquettes formed by floating macrophyte residues of the species Eichhornia crassipes (aguapé) and gypsum residues was evaluated. This mixture is recommended to avoid the presence of incrustations in the walls of the furnaces, reducing the stopping time of the furnace for cleaning and maintenance. Associated with its great proliferation capacity in aquatic environments (rivers and lakes), the floating macrophytes of the Eichhornia crassipes variety, known as hyacinth or water hyacinth, present a great potential of energy production by direct burning. At the same time, this type of biomass presents restrictions to its use as a producer of biogas and, consequently, biofertilizer. In the latter case there is a drawback which is the fixation by these aquatic macrophytes in their tissues of heavy metals. In order to avoid that a considerable amount of the biomass, which does not undergo oxidation due to lack of homogenization between the components of the combustion, or is already oxidized inside the furnace, causes incrustations that reduce the thermal capacity of the equipment, it was opted for Addition of gypsum residues to the material used to make the aguapé briquettes. Statistical analysis of the experiments assisted in the definition of suitable proportions of the mixture to reduce the adhesion of undesirable materials in the walls of the furnace and to maintain considerable values for the calorific value of said biomass. There was a decrease in the calorific value with the increase of the gypsum content in the composition of the briquettes. The maximum percentage of 4.0% m / m can be used as dosage of gypsum residue. In this case, the briquettes of macrophytes can be used as solid fuel with similar calorific power. The survey of these types of waste in the metropolitan area of Recife, together with the City of Recife / PE, showed that the availability of these Guarantee the production of heat to serve small businesses such as potteries and bakeries, contributing to the development of social and environmental activities of this capital.